P151 NEVER SMOKER WITH ESOPHAGEAL SQUAMOUS-CELL CARCINOMA: DIFFERENT DEMOGRAPHICS BUT COMPARABLE SUVIVAL. (23rd November 2019) - Alexandru, Lintis; Thibault, Voron; Vincent, Drbay; Marguerite, Messier; Clarisse, Eveno; Guillaume, Piessen
Abstract: Aim: To assess clinical characteristics, tumor behavior and long-term of esophageal squamous-cell carcinoma in never-smoker (NS) and smoker (or former smoker) (S) patients. Background & Methods: Despite a progressive decrease in the incidence of esophageal squamous-cell carcinoma (ESCC) in Europe since decades, related to the decrease in smoking, new cases of ESCC are observed in patients who have never smoked. Similar cases are described for head and neck cancers and non-small cell lung carcinomas, for which increased radiosensitivity and favorable prognosis is described. We conducted a retrospective analysis on single-center prospectively maintained database, including all patients undergoing esophagectomy for ESCC between 2010 and 2017. The primary endpoint was overall survival(OS). Secondary endpoints included disease-free survival(DFS), pathological response to preoperative treatment according to Mandard's classification (Tumor Regression Grade; TRG) and clinical characteristics of patients. Results: Three hundred and two patients underwent esophagectomy for ESCC during study period, 57 in NS group and 245 in S group. Esophageal cancers in NS patients were more frequently observed in women (68.4% vs 20%;p<0.001) and older (65.42 vs 60.69; p<0.001) than patients in S group. Tumor location (ie. cervical, upper third, middle third, lower third/EGJ) was similar between the 2 groups. Neoadjuvant radiochemotherapy was more frequently performed in S group (64.2% vs 49.1%;p=0.035) and malnutrition was less frequent in NS group (6.3% vs 20.9%;p=0.05). Tumoral characteristics (usT and usN) were comparable between the 2 groups. Pathological response to preoperative radichemotherapy was similar between NS and S group: (TRG1-2: 53.8% vs 53.7%). Postoperative complications were more frequent in S group (77.4% vs 63.2%;p=0.024), with more postoperative deaths (5.8% vs 0; p=0.080). NS patients had better OS than S patients, without reaching significance (mean survival: 46.1±4.7 months vs 35.9±2.0 months;p=0.080), and better DFS (40.0±5.3 months vs 30.0±2.1;p=0.077) Conclusion: Esophageal squamous cell carcinoma in never-smoker is characterized by low male-female sex-ratio, reduced post-operative morbidity and mortality. However, pathological response to preoperative radiochemotherapy and long-term outcomes seem to remain unaffected by tobacco use.